German vocabulary drills - Stillman, David M.; Godor, Daniele D.; Gordon, Ronni L. (New York McGraw-Hill Education, 2015)
"German Vocabulary Drills is filled with the information and practice you need to dramatically expand your language skills. It features essential German words grouped into similar themes such as daily life, food, house and home, travel, holidays, technology, arts, and the economy, helping you to grasp meanings and terms more easily. The unique presentation of vocabulary in context bridges the gap between words and conversation. You can practice your new vocabulary with more that 100 written exercises, including fill-in-the-blank, matching, translation, and composition. Plus, German Vocabulary Drills provides access to an exclusive flashcard app for use on your smartphone--a convenient, on-the-go tool for reinforching what you have learned."--Provided by publisher.
"Perfect for beginning and intermediate learners!"--Cover.
English and German.
Keywords: German language -- Vocabulary; German language -- Textbooks for foreign speakers -- English